Batuques de re-existência. Performances afrodescendentes e espaços negros em Campinas - D'Esposito, Ingrid (Confluenze. Rivista di Studi Iberoamericani, 2019)
The present article focuses on the Comunidade Jongo Dito Ribeiro, proposing an analysis that highlights the articulation between performances, identity and space – a fundamental articulation in contemporary ethno-political processes of identity emergence that, in the urban context, have acquired a strong political role, claiming the black presence within the Brazilian society. Concurrently, the performances – not descriptive, but performative practices – negotiate and transform the public space, making temporary and enduring black spaces of resistance, or metaphorical-cultural urban quilombos.